Strategi Guru dalam Menanamkan Kemandirian pada Anak Kelompok A di TK Dharma Indria II Kabupaten Jember - Jannatin Masruroh (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The background of this study arises from the condition of independence of children in group A which shows very positive development. This is reflected in the behavior of children in group A1 who are able to carry out various activities independently in the school environment, such as coming without being accompanied by parents, being able to put on and take off their own shoes, completing learning assignments without assistance, disposing of trash in the right place, washing hands independently, and eating without assistance. This kind of independence needs to be cultivated from an early age because it is the foundation in forming intelligent, confident, and responsible children. This study aims to explore and describe various strategies implemented by teachers in instilling the values of independence in children in group A at Dharma Indria II Kindergarten located in Jember Regency. The study was conducted with a qualitative approach using descriptive methods. The subjects in this study consisted of 11 children. The data collection process was carried out through direct observation in the field, in-depth interviews with related parties, and collecting supporting documents. From the results of the study, teachers in fostering children's independence include implementing routines that are carried out repeatedly (habituation), providing real examples through direct actions and role models, and establishing collaboration with parents to strengthen implementation at home. All the strategies implemented have been proven to provide good results in forming an independent attitude in children, which is shown by the consistent development of children's independence.
reupload 2026 Rudi H, FINALISASI oleh Agus 2026 Juni 08
Keywords: Teacher strategies; independence; early childhood